Effect of calendaring temperature on microstructure and properties for Li-ion batteries cathode - SHAO Haitao; YAN Huajun; WANG Wei; WU Han; YUAN Zhenge; CUI Liansen (Cailiao gongcheng)
To investigate the relationship between calendaring temperature and the microstructure and performance of cathode for Li-ion batteries （LIBs）， two kinds of cathodes at calendaring temperatures of 25 ℃ and 150 ℃ were prepared by two-high rolling mill， respectively. The effects of calendaring temperature on microstructure， thickness consistency， mechanical， and electrochemical properties of cathode were studied. The results show that with the increasing calendaring temperature， the compaction density of cathode coating particles increases significantly， the pore size is smaller， the carbon adhesive phase is uniformly distributed on the active particles， the coating particles are broken， cracks， holes， and other defects decrease， and the cathode structure of conductive/bonding network is easier to form. Compared with the room-temperature calendaring cathode， the thickness consistency of hot calendaring cathode is improved， the rebound rate is reduced by 50%， and the pole sheet bond strength increases from 182.77 N/m to 237.37 N/m， increasing 29.87%. The tensile strength increases from 20.47 MPa to 24.44 MPa， increasing 19.39%. The electrode resistivity decreases from 158.05 Ω·cm to 119.41 Ω·cm， decreasing 24.45%. The electrical conductivity increases from 0.63 S/m to 0.84 S/m， increasing 33.33%. After being assembled as LIBs， the electrochemical performance of the hot calendaring cathode is better than that of the room-temperature calendaring cathode. The cycling capacity retention increases by 18.65%. The cathode performance can be improved moderately by adjusting the calendaring temperature and other technological parameters， providing a research basis for optimizing cathode performance during the LIBs electrodes industrial preparation.